Performance of gelatin-starch edible films plasticized with glycerol: article / Amirah Abidin and Norasmah Mohammed Manshor - Abidin, Amirah; Mohammed Manshor, Norasmah (2017)
Edible polymer film can be prepared by three type of based-forming film. They are polysaccharides, proteins, and lipid based edible films. Plasticizer is use to enhance the properties of the based-forming substances. Different type of plasticizer gives different improvement on the properties of the edible films. The purpose of this report is to study the properties of edible film produced from gelatin and potato starch and glycerol is choose as the plasticizer. The film was prepared by mixing gelatin and starch with water at different concentration to form a solution. After that, plasticizer was added to the solution and was pour into plate and dried to form a film. Properties that been study were thickness, tensile strength, elongation, color, water vapor permeability, solubility and chemical composition. From the study conduct using potato starch-gelatin film plasticized with glycerol, with the variation concentration of potato starch by 1ml to 4ml for each film, the thickness of the film varies from 0.5mm to 0.6mm. While for the tensile strength of the film is decreasing with the increasing of potato starch amount, and the elongation percentage is increasing. The other properties that been discussed were solubility of film and the water vapor permeability were both decreasing with the increasing of potato starch amount in each film.